(untitled) - Ammann, Manuel (New York, 2001)
This book offers an advanced introduction to the models of credit risk valuation. It concentrates on firm-value and reduced-form approaches and their applications in practice. Additionally, the book includes new models for valuing derivative securities with credit risk, focussing on options and forward contracts subject to counterparty default risk, but also treating options on credit-risky bonds and credit derivatives. The text provides detailed descriptions of the state-of-the-art martingale methods and advanced numerical implementations based on multi-variate trees used to price derivative credit risk. Numerical examples illustrate the effects of credit risk on the prices of financial derivatives.
Keywords: Credit ratings,Credit,Risk management,Quản trị rủi ro,Tín dụng; Management,Quản trị